Actinomycetes from mangrove soils. Antagonism against phytopathogens of Sechium edule (Jacq.) Sw.) - Alejandre-Rosas, Jorge; Vallejo-Rosas, Jessica M.; Ochoa-Álvarez, Norma A.; Alvarado-Mávil, Alejandra; Ledea Rodríguez, José L. (Ecosistemas y Recursos Agropecuarios, 2025)
Sechium edule (Jacq.) Sw.) is a plant native to Mesoamerica known in Mexico as “Chayote,” and its fruits are affected postharvest by Fusarium. The objective of the present study was to evaluate the antagonistic potential of actinomycetes isolated from mangrove soils in Tuxpan, Veracruz, Mexico against phytopathogenic fungi of chayote fruit in postharvest. Fusarium spp. was isolated from post-harvest Chayote fruits, and actinomycetes from mangrove soil in Tuxpan, Veracruz, Mexico, both were classified using taxonomic keys. Three isolates of Fusarium spp were obtained (FC1, FC2, FC3). and eight of actinomycetes (A1, A2, A3, A4, A5, A6, A7, A8). The FC2 isolate of Fusarium spp. showed the greatest (P ≤ 0.05) radial growth, and in the in vitro antagonism test the responses of the actinomycetes were variable depending on the pathogen, with the isolates of actinomycetes A2, A4, A5 and A6 generally standing out, for which suggesting that the specific pathogen plays a role relevance and defines the antagonistic effect of each actin with its pathogenicity capacity. In the antagonism test through the production of volatile compounds (VOCs), isolates A2, A6 and A8 were the best performers, the magnitude of the responses in inhibition varied between 73-86.7% but without being able to differentiate (P≥0.05) among actinomycete isolates. Actinomycete isolates from mangrove soils in Tuxpan, Veracruz, Mexico act as antagonists against strains of Fusarium spp. that affect the chayote fruit (Sechium edule (Jacq.) Sw.) in post-harvest.